A critical review of technologies, costs, and projects for production of carbon-neutral liquid e-fuels from hydrogen and captured CO2. (1st September 2022) - Singh, Harpreet; Li, Chengxi; Cheng, Peng; Wang, Xunjie; Liu, Qing
Abstract : Hydrogen (H2 ) production along with CCUS (carbon capture, utilization, and storage) are two key areas for transition to net-zero emission. Carbon-neutral liquid e-fuels produced from H2 and captured CO2 are practical alternatives to fossil fuels. Abstract : Hydrogen production along with CCUS (carbon capture, utilization, and storage) are two critical areas towards decarbonization and transition to net-zero from the current fossil fuel-based energy system. Although some technical challenges and relatively high costs of these technologies are the limiting factors for their wide-scale use in the short term, the other challenge in the mass-adoption of these technologies is the lack of the hydrogen- and CO2 -compatible midstream (transport, pipelines, storage, etc. ) and downstream (engines, turbines, etc. ) infrastructure, especially as it is related to the scale required for their wide adoption. The widespread infrastructure to support the large-scale hydrogen (H2 ) economy with CCUS is not expected to be ready before 2030 in any part of the world, although the social and legal obligations to decarbonize energy and other infrastructure-heavy sectors are moving much faster. The lack of compatible midstream and downstream infrastructure is limiting the large-scale utilization of H2, and captured CO2 can be partially offset by producing sustainable liquid electro-fuels (e-fuels) derived from H2 and captured CO2 . The carbon-neutral liquid e-fuels derived from H2 and captured CO2 are attractive for multiple reasons, which include (i) being compatible with existing infrastructure for storage and transportation, (ii) being compatible with existing internal combustion engines in aviation, shipping, freight, etc., without requiring any modification to the engine or other equipment, (iii) being low in sulfur and being also able to be mixed with kerosene produced using fossil fuel, and (iv) huge transport market for their fossil fuel-based counterparts, with potential for greater long-term returns in view of their contribution in reducing carbon emissions from this sector. In terms of the technology readiness level and the field experience, liquid e-fuels have been produced at various pilot and industrial scales worldwide without any technical barriers. This study reviews a large number of technologies for H2 production (16 technologies), CO2 capture (7 technologies), their performance data, and the costs. Further, this study reviews the processes, including reactions, catalysts, and costs, to produce two liquid e-fuels (e-methanol and e-kerosene) that can be used as carbon-neutral alternatives to their fossil fuel-based conventional counterparts. The current and future projects for commercial production of liquid e-methanol and e-kerosene are also reviewed. Finally, the outlook and challenges to produce liquid e-fuels are discussed along with recommendations.